ANALISIS PEMANFAATAN PEKARANGAN UNTUK MENDUKUNG KETAHANAN PANGAN DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU YARD UTILIZATION ANALYSIS IN SUPPORT OF FOOD SECURITY INRUMBAI PESISIR PEKANBARU - Niken Nurwati; Surtinah surtinah; Amalia Masykur (Jurnal Ilmiah Pertanian, 2015)
ABSTRACT The purpose of this study was to analyze the utilization of the yard in the District Rumbai PesisirPekanbaru , and to determine the barriers and potential utilizationof the yard in the district of Rumbai Pesisir Pekanbaru . The research was conducted by survey method . The unit of analysis in this study is the household .The data collected in this study consisted of primary data and secondary data . Sampling by stratified random sampling based on the average area of thebuilding and its grounds in the selected villages . Analysis of sample identity data , utilization of the yard done descriptively , while revenue from the yard analysis performed using formulas . TR = Y.Py. Net income of farm yard using the formula : I = TR - TC . The utilization of research results in the District Rumbai yard Pesisir city of Pekanbaru , for vegetables , fruit and food crops is low , and the District Rumbai Pesisir of Pekanbaru City potential for increased utilization ofthe yard , especially commodity shallow root vegetables in a narrow area . Fruit crops and food crops for land area.